Pengaruh Pembiayaan Murabahah Dan Pembiayaan Musyarakah Terhadap Return On Asset (Roa) Pada Pt Bank Sumut Kcp Syariah Karya Periode 2018-2021 - Latifah, Latifah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2024)
This research was conducted with the aim of analyzing the effect of murabahah financing and musyarakah financing on the return on assets of PT Bank Sumut KCP Syariah Karya. The method used in this research is descriptive quantitative method. In this study there are three variables consisting of two independent variables and one dependent variable. The independent variables in this study are murabaha financing and musyarakah financing while the dependent variable is return on assets. The results of this study indicate that partially murabahah financing has no effect on ROA but musyarakah financing has a negative effect on ROA, while simultaneously murabahah financing and musyarakah financing has a positive effect and significant to return on asset.